Special issue: ‘Ethics, care and quality in educational development’ - Hlengwa, Amanda; Leibowitz, Brenda (Critical Studies in Teaching and Learning, 2023)
Editorial for the special issue of Critical Studies in Teaching and Learning, on Ethics, care and quality in educational development, guest edited by Prof Brenda Leibowitz and Dr Amanda Hlengwa.